2002
DOI: 10.1002/1616-3028(20020418)12:4<286::aid-adfm286>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Silicalite-1 Zeogrid: A New Silica Molecular Sieve with Super- and Ultra-Micropores

Abstract: Spherical, micrometer‐sized particles with a layered structure were obtained by precipitation of a Silicalite‐1 zeolite nanoslab suspension upon addition of cetyltrimethylammonium bromide (CTMABr) and subsequent calcination. The material had a specific micropore volume of 0.69 cm3 g–1, distributed over super‐ and ultra‐micropores. The formation process of this peculiar microporous solid was studied using X‐ray diffraction (XRD), 29Si MAS NMR spectroscopy, thermogravimetry (TG), and nitrogen adsorption. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
41
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 10 publications
7
41
0
Order By: Relevance
“…Over the last couple of years, several simple and reliable approaches have been developed to form micro/mesoporous combined materials using zeolite nanoparticles or zeolite seeds as the silica source [31][32][33][34][35][36]. However, most of the published reports on composite catalysts have focused on one-dimensional materials (such as MCM-41 or SBA-15) as the mesostructured component, although three-dimensional materials, such as cubic MCM-48, are more interesting from the viewpoint of catalysis due to the interwoven pore system, which allows the sufficient diffusion of reactants within the pores, subsequently leading to a better catalytic performance [37].…”
Section: Introductionsupporting
confidence: 46%
See 1 more Smart Citation
“…Over the last couple of years, several simple and reliable approaches have been developed to form micro/mesoporous combined materials using zeolite nanoparticles or zeolite seeds as the silica source [31][32][33][34][35][36]. However, most of the published reports on composite catalysts have focused on one-dimensional materials (such as MCM-41 or SBA-15) as the mesostructured component, although three-dimensional materials, such as cubic MCM-48, are more interesting from the viewpoint of catalysis due to the interwoven pore system, which allows the sufficient diffusion of reactants within the pores, subsequently leading to a better catalytic performance [37].…”
Section: Introductionsupporting
confidence: 46%
“…However, M41S materials generally exhibit weak acidity and low hydrothermal stability due to their amorphous frameworks. As a consequence, new synthesis strategies have been developed to obtain materials which com-bine the advantages of mesoporous materials and those of zeolites [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. For example, Corma et al [21] reported a post-synthesis dealumination process via steaming or acid leaching on full-grown zeolites.…”
Section: Introductionmentioning
confidence: 42%
“…The presence of a dual microporosity, viz. a combination of ultra-and super-micropores was evidenced with nitrogen adsorption isotherms at 77 K [17]. Zeogrid exhibits molecular shape selectivity in chromatographic separations of mixtures of branched and linear alkanes [17].…”
Section: Introductionsupporting
confidence: 45%
“…Empty spaces left laterally between nanoslabs are responsible for the formation of well-defined slit-shaped super-micropores, with a characteristic height of ca. 1.4 nm [17]. The presence of a dual microporosity, viz.…”
Section: Introductionsupporting
confidence: 43%
See 1 more Smart Citation